LEVEL OF KNOWLEDGE OF DENTAL STUDENTS IN RELATION TO THE STERILIZATION PROCESS BY HUMID HEAT - Alves Rocha, Marcia Regina [UNESP]; Fermino Amorin Silva, Aparecida de Fatima; Chova, L. G.; Martinez, A. L.; Torres, I. C. (Iated-int Assoc Technology Education A& Development, 2016)
The objective of this research is to identify the level of information the dental students in relation the process sterilization of items by humid heat. Field research, descriptive, exploratory, quantitative sample that used the students of the last year of dentistry at a private university in Sao Paulo State. Data collection was performed after approval by the ethics of the project and after signing the consent committee. Was conducted through a questionnaire with closed multiple choice questions. The treatment of the results was performed by percentage relative frequency. Of the 42 survey participants 67% consider themselves prepared for carrying out the sterilization of materials and only 33 % were not. Of the 9 specific questions about the autoclaving process, only 40% of question are answered correctly and more 60% of respondents answered incorrectly addressed issues. Cleaning material 76% use enzymatic detergent. Only 5% of students identified the correct temperature for this process; 12% are unaware of the biological and chemical tests which are essential in the process. Given that students do not follow the sterilization of their instruments, is understandable difficulty in recognizing and identifying the correct for autoclave sterilization parameters. This result demonstrates that students have more difficulty absorbing contents which do not apply in practice during their training. We conclude that students show insufficient to sterilize materials by autoclaving properly without risk knowledge. The school must review their teaching learning process since it has not allowed the experiences of this practice still in training.
Keywords: Sterilization by Humid Heat; Sterilization; Dentistry